Uma investigação empírico-exploratória acerca da causalidade dos indicadores operacionais de call center com a satisfação dos clientes - Oliveira, Alexandre Ferreira (2006)
Year after year the call center industry comes presenting high growth, either in Brazil or the world, using increasing contingent of people and receiving large amount of financial resources. Supporting all this industry, exists a theoretical reference that privileges the search of the improvement of diverse operational performance indicators. This study, empirically examines the relationship between caller satisfaction and diverse operational performance indicators currently used for call center management in Brazil. For in such a way, a group of telecommunications segment call centers will be used searching to determine which indicators are really more significantly correlated with the customer satisfaction. Of this form, it is aimed at to add new evidences and explanations to existing literature, in way that companies of call center industry can give a more adequate service to their customer, opposite to solely focus its efforts in the improvement of a great set of performance pointers that, effectively, can not become related with the customer satisfaction.